Prevalencia de fasciolosis en bovinos de Costa Rica (2014). Comparación de cuatro técnicas para su diagnóstico [Prevalencia de fasciolosis en bovinos de Costa Rica (2014). Comparación de cuatro técnicas diagnósticas] - Romero-Zúñiga, Juan José (2016)
A cross-sectional study was done to determine the prevalence of fasciolosis in cattle slaughtered in abattoirs of Costa Rica and to compare 4 different diagnostic techniques (macroscopic examination of the livers, standard sedimentation of stool, standard sedimentation of the fluid of the gallbladder, and detection of copro-antigen in fecal samples. The sample was divided into two strata of probability of infection (high and low). Considering all the techniques, 11 positive samples from the stratum of high probability were found [prevalence 4.3% (confidence interval CI 95%: 1.8-6.7)] and 1 of the stratum of low probability [prevalence 0.5% (CI 95%: 0.0-1.4)]. When comparing all diagnostic methods, considering the liver condemnation as the reference method, values of sensitivity and specificity respectively of 40 and 100% for the standard sedimentation of stool, 70 and 99.8% for the standard sedimentation of the fluid of the gallbladder and 50 and 100% for the ELISA that detects copro-antigen in feces were obtained. It is concluded that the macroscopic examination of livers in slaughterhouses is a good tool for the monitoring of the disease and that this parasite is distributed heterogeneously in the country.